Understanding social workers' hidden roles in medication safety for older adults: A qualitative study. (21st April 2021) - Wagle, Kamal; Cottingham, Ann H.; Butler, Dawn; Grover, Jenny; Litzelman, Debra K.
ABSTRACT: Older adults are vulnerable to risks associated with medications. This study explores the roles of Social Workers in facilitating medication safety for older adults. Eight social workers from federally qualified health centers participated in a case-based and interactive medication safety curriculum. They participated in an in-depth, semi-structured interview to explore their roles and strategies in assisting older adults and caregivers with medication management. Findings were transcribed and analyzed. Six themes characterizing social workers' roles in medication management were identified: a) Referral: matching patients and medication-related resources within the health-care system and community; b) Communication: connecting providers, patients, caregivers, and support system; c) Access to medicine: addressing unique needs of each patient to foster their ability to obtain their medicines; d) Social Determinants of Health: investigating the social challenges of each patient and facilitating specific medication management approaches to meet identified needs; e) Engagement: engaging patients in co-developing a treatment plan; f) Caregiver Support: preparing caregivers to assist in medication management. Social workers are trained and well positioned to provide a multi-faceted approach to improve medication management for older adults. Their unique perspectives and skills are important in addressing the complex challenges of medication management.